A copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles and its application
By loading platinum nanoparticles in three-dimensional nanocomposites of copper-based metal organic frames, the problems of natural enzymes being easily lost under extreme conditions and platinum nanoparticles being easily aggregated are solved, and efficient and low-cost catalytic materials are achieved.
Patent Information
- Application Number
- CN202210156920.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-21
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-02-21
AI Technical Summary
In the prior art, natural enzymes are easily lost under extreme conditions, and are costly to prepare and purify and difficult to recover. Moreover, platinum nanoparticles are easily aggregated due to their small particle size, which affects their enzyme-like activity.
The copper-based metal organic frame three-dimensional nanocomposite material (Cu-MOF@Pt) is used as a support to support platinum nanoparticles, and Pt NPs are dispersed through the Cu-MOF frame structure to improve their stability and catalytic activity.
It effectively solves the problem of reduced catalytic activity caused by the prone aggregation of platinum nanoparticles, reduces the overall cost, and improves the stability and catalytic activity of Cu-MOF@Pt under extreme conditions.
Smart Images

Figure CN114624201B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials, and in particular relates to a copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles and an application thereof. Background Art
[0002] Natural enzymes have high specificity and high catalytic efficiency for reaction substrates, which makes them have important applications in many fields. However, the inherent defects of natural enzymes, such as the loss of catalytic activity under extreme conditions, high preparation and purification costs, and difficulty in recycling, have greatly hindered their practical application. Therefore, the development of efficient and low-cost enzyme mimics is an urgent problem to be solved.
[0003] Platinum nanoparticles (Pt NPs) are a kind of widely used precious metal nanoparticles with high peroxidase-like activity. Their activity and dispersibility are affected by particle size. The smaller the particle size, the higher the activity and the easier it is to aggregate. Aggregation of Pt NPs will also inhibit the enzyme-like activity of Pt NPs. Therefore, choosing a suitable carrier to make small particles of Pt NPs well dispersed is crucial to maintain their enzyme-like activity. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles and its application.
[0005] The technical scheme adopted by the present invention is as follows: a copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles, and its preparation process comprises the following steps: dissolving Cu(NO3)2·3H2O in DMF, adding PVP and ultrasonically distributing the system evenly to obtain a first solution system; dissolving H3BTC in DMF to obtain a second solution system; uniformly mixing the first solution system and the second solution system, then adding platinum nanoparticles, heating at 60-100°C for reaction, and after the reaction is completed, collecting solids and washing to obtain the copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles.
[0006] The copper-based metal organic framework three-dimensional nanocomposite material is an octahedron at the microscopic level.
[0007] Application of the copper-based metal-organic framework three-dimensional nanocomposite loaded with platinum nanoparticles as described above as a peroxidase-like enzyme.
[0008] The copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles as described above is used for detecting glucose, and the application is for non-disease treatment or diagnosis purposes.
[0009] A method for detecting glucose, which is for non-disease treatment or diagnosis purposes, comprises the following steps:
[0010] (1) Mixing the test solution with the glucose oxidase solution for reaction;
[0011] (2) The solution after the reaction in step (1) is mixed with a buffer solution containing the copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles as described above and TMB to obtain a reaction system, and the mixture is reacted.
[0012] After the reaction in step (2) is completed, the absorbance of the reaction system at 652 nm is measured.
[0013] When the glucose concentration in the test solution is between 2 and 15 mM, the absorbance of the reaction system at 652 nm is linearly related to the glucose concentration in the test solution.
[0014] In step (2), the pH of the reaction system is 2.5-3.5, the concentration of the copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles is ≥50 µg / mL, and the reaction is carried out at 20-30°C.
[0015] In step (2), the buffer solution is HAc-NaAc buffer.
[0016] A glucose detection kit comprises the copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles as described above.
[0017] The beneficial effects of the present invention are as follows: the present invention uses MOFs material as a carrier to load Pt NPs to generate Cu-MOF@Pt nanocomposite materials. Compared with pure Pt NPs, the problem that pure Pt NPs are easy to aggregate due to their small particle size, thereby affecting enzyme activity, is well solved. In addition, Pt, as one of the precious metal materials, is relatively expensive, and the addition of Cu-MOF reduces the overall cost.
[0018] The Cu-MOF@Pt nanocomposite material provided by the present invention can be cascaded with glucose oxidase to detect glucose, and has the advantages of high precision and high selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0020] Figure 1In the figure, (a) is the SEM image of Cu-MOF@Pt; (bd) are the TEM images of Cu-MOF@Pt under different magnifications;
[0021] Figure 2 High-resolution transmission electron microscopy (HRTEM) and mapping images of Cu-MOF@Pt;
[0022] Figure 3 This is the X-ray energy spectrum analysis (EDS) of Cu-MOF@Pt;
[0023] Figure 4 UV-visible absorption spectrum of TMB / H2O2 / Cu-MOF@Pt solution in 0.2 M HAc-NaAc buffer solution (pH 3);
[0024] Figure 5 is the relationship between the activity of Cu-MOF@Pt peroxidase and pH;
[0025] Figure 6 is the relationship between the peroxidase activity of Cu-MOF@Pt and the TMB concentration;
[0026] Figure 7 is the relationship between the peroxidase activity of Cu-MOF@Pt and the H2O2 concentration;
[0027] Figure 8 is the relationship between the peroxidase activity of Cu-MOF@Pt and the concentration of Cu-MOF@Pt;
[0028] Fig. 9 is the relationship between the activity of Cu-MOF@Pt peroxidase and temperature;
[0029] Fig.10 The absorbance of the reaction system at 652 nm was used to detect glucose using the peroxidase-like activity of Cu-MOF@Pt at different concentrations;
[0030] Fig.11 is the linear regression curve of the absorbance of the reaction system at 652 nm and the glucose concentration;
[0031] Fig.12 The selectivity of Cu-MOF@Pt for different sugars. DETAILED DESCRIPTION
[0032] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0033] Embodiment 1:
[0034] Preparation of a copper-based metal organic framework three-dimensional nanocomposite material (Cu-MOF@Pt) loaded with platinum nanoparticles:
[0035] (1) Preparation of Pt NPs: 47.628 mg of potassium hexachloroplatinate (K2PtCl6), 222 mg of polyvinylpyrrolidone (PVP, MW = 40000) and 20 mL of ethylene glycol were placed in a round-bottom flask. The round-bottom flask was fixed in an oil bath and refluxed at 180°C for 10 min to obtain a black solution. After cooling to room temperature, acetone was slowly and uniformly added to the black solution until a dark brown colloidal precipitate appeared. The obtained dark brown colloidal solution was separated by high-speed centrifugation at 8000 rpm for 5 min, washed several times with acetone and n-hexane, and then vacuum dried at 45°C overnight.
[0036] (2) Preparation of Cu-MOF@Pt nanocomposite: 43.75 mg of Cu(NO3)2·3H2O was dissolved in 7.2 mL of DMF, and then 15 mg of PVP was added and ultrasonicated for 5 min to obtain a homogeneous solution. 21 mg of H3BTC was dissolved in 3 mL of DMF. Then, the two solutions were mixed and ultrasonicated for 10 min. 10 mg of Pt NPs was added and mixed and ultrasonicated for another 10 min. Subsequently, the mixture was transferred to a polytetrafluoroethylene-lined reactor and placed in an oven at 80 °C for 24 h. The solid was collected by centrifugation and washed three times with fresh DMF and ethanol, respectively. Finally, the product was dried overnight at 60 °C in vacuum.
[0037] like Figure 1 As shown in (a), the scanning electron microscope (SEM) image shows the octahedral structure of Cu-MOF@Pt. The size and morphology of Cu-MOF@Pt were characterized by transmission electron microscopy (TEM). Figure 1 As shown in (bd), the obtained Cu-MOF@Pt is a polyhedral nanocomposite with a diameter of about several hundred nanometers. Cu-MOF is loaded with a large amount of Pt NPs, and the lattice of Pt NPs in the Cu-MOF@Pt nanocomposite is about 0.23 nm, corresponding to the interplanar spacing of the Pt(111) crystal plane.
[0038] like Figure 2 As shown, Pt NPs were uniformly grown inside the Cu-MOF@Pt nanocomposite. Figure 2 The HRTEM and Mapping images shown confirm the presence of C, N, O, Cu and Pt in the Cu-MOF@Pt nanocomposite. Each element is evenly distributed in the entire area, with no obvious element aggregation or separation, indicating that Pt NPs are evenly distributed on Cu-MOF.
[0039] The elemental composition of Cu-MOF@Pt was analyzed by EDS. Figure 3 As shown, it can be clearly seen that Cu-MOF@Pt consists of five typical peaks of C, N, O, Cu and Pt, with atomic contents of 76.31%, 0.15%, 9.64%, 13.7% and 0.2%, respectively.
[0040] like Figure 4 The ultraviolet-visible (UV-vis) absorption spectrum shown shows that the peak of Cu-MOF@Pt has no obvious change compared with that of Cu-MOF, indicating that Pt NPs grow inside Cu-MOF instead of on the surface.
[0041] Embodiment 2:
[0042] Cu-MOF@Pt, TMB and H2O2 were added to HAc-NaAc buffer solution (0.2 M, pH 3) and reacted at room temperature for a certain time. Then the absorbance of the solution at 652 nm was recorded and the corresponding photos were taken. When Cu-MOF@Pt was present, there was an obvious absorption peak at 652 nm, because Cu-MOF@Pt can catalyze the oxidation of colorless TMB in the presence of H2O2 to generate blue oxTMB color. In the absence of Cu-MOF@Pt, an almost completely flat peak appeared in the wavelength range of 550-750 nm, indicating that the oxidation effect of H2O2 on TMB is negligible.
[0043] Similar to natural enzymes, the catalytic activity of Cu-MOF@Pt is also affected by solution pH, substrate concentration, catalyst concentration, and temperature.
[0044] To investigate the effect of pH on the catalytic activity of Cu-MOF@Pt, the other parameters were set as follows: Cu-MOF@Pt concentration was 50 µg / mL, TMB concentration was 0.2 mM, H2O2 concentration was 10 mM, and reaction time was 20 min. Figure 5 As shown, the catalytic activity of Cu-MOF@Pt reaches its peak at pH 3.0.
[0045] To investigate the effect of TMB concentration on the catalytic activity of Cu-MOF@Pt, the other parameters were set as follows: Cu-MOF@Pt concentration was 50 µg / mL, pH was 3, H2O2 concentration was 10 mM, and reaction time was 20 min. Figure 6 As shown in Figure 2, the catalytic activity of Cu-MOF@Pt increases rapidly with the increase of TMB concentration.
[0046] To investigate the effect of H2O2 concentration on the catalytic activity of Cu-MOF@Pt, the other parameters were set as follows: Cu-MOF@Pt concentration was 50 µg / mL, pH was 3, TMB concentration was 0.1 mM, and reaction time was 10 min. Figure 7 As shown in Figure 2, the catalytic activity of Cu-MOF@Pt increases rapidly with the increase of H2O2 concentration.
[0047] To investigate the effect of temperature on the catalytic activity of Cu-MOF@Pt, the other parameters were set as follows: Cu-MOF@Pt concentration was 50µg / mL, pH was 3, TMB concentration was 0.1 mM, H2O2 concentration was 160 mM, and reaction time was 5 min. Fig. 9 As shown in the figure, the catalytic performance of Cu-MOF@Pt remains almost unchanged in the temperature range of 20 ~ 30℃. Above 30℃, the catalytic activity decreases rapidly with the increase of temperature. Therefore, Cu-MOF@Pt can react at room temperature.
[0048] To investigate the effect of Cu-MOF@Pt concentration on the catalytic activity of Cu-MOF@Pt, the other parameters were set as follows: pH was 3, TMB concentration was 0.1 mM, H2O2 concentration was 160 mM, and reaction time was 390 s. Figure 8 As shown, the catalytic activity increases with the increase of Cu-MOF@Pt concentration until the concentration is 50 µg / mL.
[0049] Embodiment 3:
[0050] Steady-state kinetics of Cu-MOF@Pt: Within a specific range of TMB and H2O2 concentrations, Cu-MOF@Pt can obtain a typical Michaelis-Menten curve. The enzymatic parameters Km and Vmax were calculated and summarized in Table 1. It can be seen that compared with horseradish peroxidase (HRP), the Km values of Cu-MOF@Pt for TMB and H2O2 are much lower, indicating that Cu-MOF@Pt has a higher affinity for both substrates than HRP. In addition, compared with other reported nanozymes, Cu-MOF@Pt still has a higher affinity.
[0051] Table 1. Comparison of Km and Vmax of Cu-MOF@Pt and nanozymes reported in literature for catalytic oxidation reactions
[0052]
[0053] Embodiment 4:
[0054] Based on the peroxidase-like activity of Cu-MOF@Pt, a colorimetric detection method for glucose was established. The specific steps are as follows:
[0055] (1) 10 μL of deionized water containing different concentrations of glucose and 10 μL of deionized water containing 1 mg / mL glucose oxidase (GOx) were mixed and incubated at 37°C for 30 min;
[0056] (2) 20 µL of the above solution was added to 180 µL of HAc-NaAc buffer (0.2 M, pH 3) containing Cu-MOF@Pt (400 µg / mL) and TMB solution (0.1 mM) to ensure that the final glucose concentration was 0 ~ 20 mM;
[0057] (3) After incubation for 40 min, the absorbance of the reaction mixture (200 µL) was recorded at 652 nm and photographed.
[0058] The detection principle is as follows: first, glucose oxidase is used to catalyze the oxidation of glucose to produce gluconolactone and hydrogen peroxide. The generated hydrogen peroxide can oxidize TMB in the presence of Cu-MOF@Pt to produce blue oxTMB. The amount of oxTMB generated is proportional to the glucose content. Glucose can be quantitatively detected by detecting the absorbance of the product.
[0059] like Fig.10 As shown in the figure, during the glucose detection process, the absorbance value at 652 nm increased with the increase of Cu-MOF@Pt concentration. Considering that high concentration of Cu-MOF@Pt itself is blue-green, 400 µg / mL was finally selected for subsequent experiments.
[0060] like Fig.11 As shown in Figure 2, the absorbance at 652 nm increased with the increase of glucose concentration, and a linear relationship was established between 2 and 15 mM with a good correlation coefficient (R 2 = 0.99998)( Fig.11 ) to meet the needs of clinical trials.
[0061] Fructose, lactose, maltose, and sucrose were used as controls in the glucose detection experiment to evaluate the selectivity of the method for glucose detection. The results showed that the interference of fructose, lactose, maltose, or sucrose was negligible, which means excellent selectivity ( Fig.12 ).
[0062] Embodiment 5:
[0063] Serum samples were obtained by centrifugation of whole blood from adult volunteers (3.5 krpm, 10 minutes). The samples were then diluted 1000 times with deionized water and glucose solution was added to obtain the test solution sample. The glucose in the test solution sample was then determined according to the following steps.
[0064] (1) Mix 10 µL of the test solution sample and 10 µL of deionized water containing 1 mg / mL glucose oxidase (GOx) and incubate at 37°C for 30 min;
[0065] (2) 20 µL of the above solution was added to 180 µL of HAc-NaAc buffer (0.2 M, pH 3) containing Cu-MOF@Pt (400 µg / mL) and TMB solution (0.1 mM) to ensure that the final glucose concentration was 0 ~ 20 mM;
[0066] (3) After incubation for 40 min, the absorbance of the reaction mixture (200 µL) was recorded at 652 nm and photographed.
[0067] The glucose spiked into the diluted human serum samples was measured, and the recovery of glucose in the human serum samples was calculated to be 93.5 to 102.8%, as shown in Table 2. The results show that the Cu-MOF@Pt nanocomposite cascade glucose oxidase can effectively determine glucose in real samples.
[0068] Table 2. Determination of glucose concentration in diluted human serum (n = 3)
[0069]
[0070] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A method for detecting glucose, wherein the method is for non-disease treatment or diagnosis purposes, characterized in that The following steps are involved: (1) mixing the test solution with the glucose oxidase solution for reaction; (2) mixing the solution after the reaction in step (1) with a buffer solution containing a copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles and TMB to obtain a reaction system, and reacting; After the reaction in step (2) is completed, the absorbance of the reaction system at 652 nm is measured; when the glucose concentration in the test solution is 2-15 mM, the absorbance of the reaction system at 652 nm is linearly related to the glucose concentration in the test solution; In step (2), the pH of the reaction system is 2.5-3.5, the concentration of the copper-based metal organic framework three-dimensional nanocomposite material loaded with platinum nanoparticles is ≥50 μg / mL, and the reaction is carried out at 20-30° C.; The preparation process of the copper-based metal-organic framework three-dimensional nanocomposite material containing loaded platinum nanoparticles is as follows: 43.75 mg of Cu(NO3)2·3H2O was dissolved in 7.2 mL of DMF, and then 15 mg of PVP was added and ultrasonicated for 5 minutes to obtain a uniform solution; 21 mg of H3BTC was dissolved in 3 mL of DMF; then, the two solutions were mixed and ultrasonicated for 10 minutes; 10 mg of PtNPs was added and mixed and ultrasonicated for another 10 minutes; then, the mixture was transferred to a polytetrafluoroethylene-lined reactor and placed in an oven at 80°C for 24 hours; the solid was collected by centrifugation and washed three times with fresh DMF and ethanol respectively; finally, the product was vacuum dried at 60°C overnight.
2. The method for detecting glucose according to claim 1, characterized in that: In step (2), the buffer solution is HAc-NaAc buffer.